PENGARUH MODEL PEMBELAJARAN QUANTUM LEARNING TERHADAP HASIL BELAJAR IPAS PESERTA DIDIK KELAS V SEKOLAH DASAR - Sabila, Cantika; Rabiyatul Adawiyah Siregar; Fadhillah Khairani; Frida Destini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The problem addressed in this study is the low learning outcomes in Natural and Social Sciences (IPAS) among fifth-grade students at SD Negeri 02 Rajabasa Jaya, which is caused by a teacher-centered learning process. This study aims to determine the effect of the Quantum Learning model on the IPAS learning outcomes of fifth-grade elementary school students. This research employed a quantitative approach with a quasi-experimental method using a non-equivalent control group design. The research sample consisted of the entire population, namely 34 students, selected through a non-probability sampling technique with a saturated sampling method. Data were collected through test and non-test techniques, while the data analysis technique used was simple linear regression. The results showed that the implementation of the Quantum Learning model had a positive and significant effect on the IPAS learning outcomes of fifth-grade students at SD Negeri 02 Rajabasa Jaya. This was proven by the results of the simple linear regression test, which obtained a significance value of 0.000 < 0.05 and an R Square value of 62.6%.